Personal counselor quality improvement based on An-Nahdliyah moderation value - Sa'idah, Ishlakhatus; Annajih, Moh Ziyadul Haq (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2020)
The counselor's personality is influenced by belief values (belief systems), so these values are essential to consider. Indonesia is a diverse country. Indonesian society is also a religious society. In terms of diversity and terms of religion, there is a match between the two points in the an-Nahdliyah moderation value as the majority group of Indonesian Islam. This study aims to improve the personal quality of the counselor based on an-Nahdliyah moderation values by providing training to prospective counselors. This study uses a one-group pretest-posttest design. Research subjects were 25 prospective counselors at STAI Miftahul Ulum Pamekasan with simple random sampling. The data analysis technique used a t-test. The results showed that an-Nahdliyah moderating values training for prospective counselors was effective in improving the personal quality of prospective counselors. This is evidenced by the value of increasing the personal quality of prospective counselors who fall into the medium category. This means that this training is appropriate to be used to improve the personal quality of prospective counselors in providing guidance and counseling services based on the values of tawassuth, tawazun, tasamuh, and i'tidal.